2014 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP) 2014
DOI: 10.1109/ceidp.2014.6995877
|View full text |Cite
|
Sign up to set email alerts
|

Study and analysis of conduction mechanisms and space charge accumulation phenomena under high applied DC electric field in XLPE for HVDC cable application

Abstract: The development of High Voltage Direct Current (HVDC) cables requires design according to specific criteria and materials with appropriate properties. Cross-linked polyethylene (XLPE) has established itself over the past 20 years as the most used insulation material for HVAC cables, but also more recently for HVDC cables. If the electrical properties of this polymer have been widely studied under AC stress, the behavior of these materials under high DC stress is less known and needs thorough investigation. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Electrical volume resistivity values measured during ageing conditions under 30 and 60 kV/mm at 70, 80 and 90 • C for 857 days are presented in [22,23]. Electrical volume resistivity did not show any significant evolution as a function of ageing time, for all temperatures and electric fields studied [22].…”
Section: Electrical Volume Resistivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical volume resistivity values measured during ageing conditions under 30 and 60 kV/mm at 70, 80 and 90 • C for 857 days are presented in [22,23]. Electrical volume resistivity did not show any significant evolution as a function of ageing time, for all temperatures and electric fields studied [22].…”
Section: Electrical Volume Resistivitymentioning
confidence: 99%
“…Electrical volume resistivity values measured during ageing conditions under 30 and 60 kV/mm at 70, 80 and 90 • C for 857 days are presented in [22,23]. Electrical volume resistivity did not show any significant evolution as a function of ageing time, for all temperatures and electric fields studied [22]. In this section, we present only results for ageing tests under 30 kV/mm and 60 k V/mm at 90 • C. Values for ageing under 30 kV/mm measured under 2 kV/mm were between 10 14 Ω × m and 10 15 Ω × m, whatever the ageing temperature, while those measured under 30 kV/mm were lower than those under 2 kV/mm and are on average of the order of 10 12 Ω × m and 10 13 Ω × m. For ageing under 60 kV/mm, electrical volume resistivity was in the order of 10 14 Ω × m and 10 15 Ω × m when measured under 2 kV/mm, and between 10 13 Ω × m and 10 15 Ω × m when measured under 30 kV/mm.…”
Section: Electrical Volume Resistivitymentioning
confidence: 99%
“…The obtained results have shown that the space charge accumulation grows with the increase of both electric field and temperature. 48 …”
Section: The Thermal Step Methods Under Applied DC Fieldmentioning
confidence: 99%
“…Dielectrics are widely used as insulators in electrical engineering and are subjected to many constraints: temperature, electric field, and pressure . The insulating properties of these dielectrics can then be modified under these constraints.…”
Section: Introductionmentioning
confidence: 99%